Becoming Taiwanese : ethnogenesis in a colonial city, 1880s to 1950s - Dawley, Evan N. (Harvard East Asian monographs, 2019)
"Examines the first era of Taiwanese identity construction, the first half of the twentieth century, in a place that served as a crucible for new identities, the northern port city of Jilong (Keelung). Part colonial urban social history, part exploration of the relationship between modern ethnicity and nationalism, offering important new answers to questions of ethnic identity formation"--Provided by publisher.